Method of creating sheet in which aggregated synthetic resin hollow balls with hollow ball skins bonded together using friction heat are covered with aggregated carbon black bonded together using friction pressure welding
Patent Information
- Application Number
- JP2023131225
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
AI Technical Summary
【0016】 つまり、7段落に記載した方法で作成したシートを、基材ないしは部品の表面の予め決めた位置に配置させ、シートの表面全体に圧縮応力を均等に加える。最初に、シートの表面を覆った摩擦圧接で接合したアグリゲートの集まりが、基材または部品の表面と接触する。次に、基材または部品の表面と接触する摩擦圧接で接合したアグリゲートの集まりの一部が弾性変形し、弾性変形した摩擦圧接で接合したアグリゲートの集まりの一部が、基材または部品の表面の凹凸の凹部に入り込み、表面の凹部を埋める。これによって、摩擦圧接で接合したアグリゲートの集まりが、基材または部品の表面と接触する接触部に隙間がなくなる。さらに、圧縮応力が加わると、既に接触部に隙間がなくなっているため、摩擦圧接で接合したアグリゲートの集まりが、基材または部品の表面と接触する接触部に摩擦熱が発生する。この摩擦熱によって、シートの表面を覆った摩擦圧接で接合したアグリゲートの集まりが、基材または部品の表面に接合する。 つまり、基材ないしは部品の表面の凹凸は、大きさがサブミクロンと小さいが、シートの表面と接触する凸部は莫大な数からなる。従って、基材ないしは部品の表面に配置したシートの表面を均等に圧縮すると、次の現象が連続して起こる。最初に、摩擦圧接で接合したアグリゲートの集まりが、基材ないしは部品の表面と接触する。次に、摩擦圧接で接合したアグリゲートの集まりの接触部の一部が僅かに弾性変形し、弾性変形した接触部の一部が基材または部品の表面の凹凸の凹部に入り込み、表面の凹部を埋める。これによって、基材または部品の表面と摩擦圧接で接合したアグリゲートの集まりが接触する接触部に隙間がなくなる。さらに、圧縮応力が加わると、既に接触部に隙間がなくなっているため、基材または部品の表面と摩擦圧接で接合したアグリゲートの集まりが接触する接触部に摩擦熱が発生する。この摩擦熱で、摩擦圧接で接合したアグリゲートの集まりが、基材ないしは部品の表面の凹凸に接合する。いっぽう、基材ないしは部品の表面の接触部である凹凸の数が莫大な数で、凹凸の間隔が僅かな距離である。このため、摩擦圧接で接合したアグリゲートの集まりが、基材ないしは部品の表面に強固に接合する。いっぽう、摩擦圧接で接合したアグリゲートの集まりは、摩擦熱で接合した中空ボールの集まりに強固に接合している。これによって、シートが、基材ないしは部品の表面に強固に接合する。 なお、接触部に発生する摩擦熱は、瞬間的に発生し、この後、短時間で冷却する。このため、基材ないしは部品が、耐熱性の低い合成樹脂であっても、また、布帛、ないしは、不織布であっても、シートが、基材ないしは部品の表面に接合する。従って、シートは、様々な材質からなる基材ないしは部品に対し、摩擦圧接という極めて簡単な手段で接合できる。この結果、7段落に記載したシートの様々な性質が、様々な材質からなる基材ないしは部品の表面に付与される。
Smart Images

Figure 2025025944000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention is a method for producing a sheet in which a collection of hollow balls, each of which has its skin bonded together by frictional heat, is covered with a collection of carbon black aggregates bonded together by friction welding. This produces a lightweight sheet that has the light-blocking, heat-dissipating, and conductive properties that the collection of carbon black aggregates possess. In other words, the total light transmittance of carbon black is small at 0%. Therefore, the aggregates of carbon black bonded by friction welding have excellent light shielding properties. Therefore, even if ultraviolet rays are continuously irradiated, the aggregates of synthetic resin hollow balls bonded by friction heat will not deteriorate. In addition, carbon black has a high thermal emissivity of 0.95-0.97, which is the ratio to the thermal radiation of a black body. Therefore, the aggregates of carbon black bonded by friction welding have excellent heat dissipation properties. Furthermore, the resistivity of carbon black is six orders of magnitude higher than the resistivity of metals, but 13 orders of magnitude lower than the resistivity of synthetic resins. Therefore, based on the conductivity of carbon black, the aggregates of carbon black bonded by friction welding have the functions of conductivity, electromagnetic shielding, and antistatic properties. In addition, since aggregates made of carbon particles have excellent corrosion resistance, the aggregates of carbon black bonded by friction welding have excellent corrosion resistance. This gives the group of hollow balls, whose skins are bonded together by frictional heat, excellent light blocking properties, excellent heat dissipation properties, electrical conductivity, electromagnetic wave shielding properties, antistatic properties, and excellent corrosion resistance. In addition, because the insides of the hollow balls are filled with air, the sheet is lighter than a synthetic resin sheet of the same size and thickness.
[0002] The present inventor has filed an invention in which a synthetic resin pellet is covered with a collection of aggregates and the pellet is used to mold a synthetic resin molded body that combines light blocking, heat dissipation, and electrical conductivity according to a conventional synthetic resin molding method. The invention is filed in Japanese Patent Application No. 2023-011433. In the present invention, a collection of hollow balls, in which the skins of the hollow balls are bonded together by frictional heat, is covered with a collection of carbon black aggregates bonded together by friction welding, so the synthetic resin sheet, which has light-shielding properties, heat dissipation properties, and electrical conductivity, is lighter than the sheet of the prior application. Furthermore, the sheet can be produced more cheaply than in the prior application, because the skins of the hollow balls are bonded together by frictional heat simply by raising the temperature of the collection of hollow balls in contact with each other. [Background technology]
[0003] The prior art closest to the present invention is a technique for imparting light-shielding properties to synthetic resins. For example, Patent Document 1 is a patent that provides light-blocking properties to a synthetic resin container by covering the outside of the synthetic resin container with a foam consisting of many bubbles. However, there is no description at all as to why a foam consisting of many bubbles provides light-blocking properties. Patent Document 2 describes forming a synthetic resin container by extrusion blow molding and providing a light-shielding layer on the inner surface of the container body, but does not provide any specific description of the light-shielding layer, and therefore does not provide any description of why the light-shielding layer provides light-shielding properties. On the other hand, it is known that the molecular structure of polymeric materials, not limited to synthetic resins, is destroyed by ultraviolet rays, causing the polymeric materials to deteriorate. However, Patent Document 1 does not state anything about the relationship between the light-shielding properties and the foam, and Patent Document 2 does not state anything about the light-shielding properties and the configuration of the light-shielding layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2022-119649 A [Patent Document 2] JP 2020-183281 A [Non-patent literature]
[0005] [Non-Patent Document 1] According to the "List of tensile strength of plastics" listed on WWW.toishi.info, a comprehensive information site on whetstones, grinding and polishing. DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0006] The problems that the present invention aims to solve are, first, to find a method for producing a sheet made of a synthetic resin having light-shielding properties that is lighter than a sheet made of a synthetic resin molded body. This will broaden the uses of the sheet made of a synthetic resin having light-shielding properties. Second, to find a method for producing a sheet made of a synthetic resin having light-shielding properties that is less expensive than a sheet made of a synthetic resin molded body. This will further broaden the uses of the sheet made of a synthetic resin having light-shielding properties. Third, it is possible to impart functions other than light-shielding properties to the sheet made of a synthetic resin. This will further broaden the uses of the sheet made of a synthetic resin. These three problems are the problems that the present invention aims to solve. [Means for solving the problem]
[0007] The method for producing a sheet in which a group of synthetic resin hollow balls bonded by frictional heat are covered with a group of carbon black aggregates bonded by friction welding is as follows: A collection of synthetic resin hollow balls of the same shape and size is placed in a first container having a bottom shape that is the same as the shape of the sheet to be produced, and the skins of all of the hollow balls are brought into contact with each other in the collection of hollow balls, and the collection of hollow balls is arranged in a plane as a collection of hollow balls in a single layer throughout the first container. Thereafter, a plate material that covers the entire collection of hollow balls is placed on top of the collection of hollow balls, and multiple weights are placed at equal intervals on the surface of the plate material to uniformly compress the collection of hollow balls. a first step of heating the first container to a predetermined temperature, whereby the air inside the hollow balls thermally expands, causing the skins of adjacent hollow balls to come into contact with each other and generating frictional heat at the contact points, and the contact points are bonded together by the frictional heat to form a group of hollow balls bonded together by the frictional heat; thereafter, removing the weight and the plate material; and further, simultaneously applying the same impact acceleration to multiple locations on the reverse side of the bottom surface of the first container to peel off the group of hollow balls bonded together by the frictional heat from the bottom surface of the first container, and removing the group of hollow balls bonded together by the frictional heat; A carbon black cluster and methanol in an amount greater than the weight of the carbon black cluster are placed in a second container, the methanol is stirred, and the carbon black clusters are immersed in the methanol. Thereafter, a plate material covering the entire surface of the carbon black clusters is placed on the carbon black clusters, and a compressive load is applied evenly to the entire surface of the plate material to crush the carbon black clusters immersed in the methanol. The second container is placed on a vibration table of a vibrator, the vibrator is operated, and vibration accelerations in three directions, front-back, left-right, and up-down, are repeatedly applied to the second container to rearrange the crushed carbon black clusters in the methanol. Thereafter, the plate material is placed on the carbon black clusters again, and the compressive load is applied evenly to the entire surface of the plate material again to further crush the crushed carbon black clusters in the methanol. and then, repeatedly applying the vibration acceleration in the three directions to the second container again. The pair of processes consisting of the process of applying the compressive load and the process of applying the vibration acceleration are repeated, and when a repulsive force is generated in the plate material when the compressive load is applied to the plate material, it is determined that the crushing of the carbon black clumps in the methanol is completed, and the pair of processes are stopped. Thereafter, the plate material is removed from the second container. A second process includes disposing a homogenizer device in the second container and operating the homogenizer device to repeatedly apply shock waves via the methanol to the crushed carbon black clumps, thereby separating entanglements between aggregates in the crushed carbon black, entangling the aggregates with each other via the methanol, and preparing a suspension in which the entangled aggregate clumps are dispersed in methanol. a third process in which the collection of hollow balls joined by frictional heat produced in the first process is placed in a third container having a bottom larger than the collection of hollow balls joined by frictional heat and each of the plate materials constituting the four side surfaces has a function of moving parallel to the inside of the container in a direction perpendicular to the side surfaces, so that a gap of the same size is formed between the collection of hollow balls joined by frictional heat and the four side surfaces; further, a part of the suspension produced in the second process is poured into the third container to immerse the collection of hollow balls joined by frictional heat in the suspension; thereafter, the third container is placed on the vibration table of the vibration exciter used in the second process, the vibration exciter is operated, and vibration accelerations in three directions, front-back, left-right, and up-down, are repeatedly applied to the third container; thereby, the suspension is filled in all gaps in the collection of hollow balls joined by frictional heat, and the suspension is interposed between the collection of hollow balls joined by frictional heat and the bottom surface of the third container; and further, the collection of hollow balls joined by frictional heat is immersed in the suspension; A plate material that covers the entire surface of the group of hollow balls bonded by frictional heat placed in the third container that has completed the treatment in the third step is placed on the group of hollow balls bonded by frictional heat, and a compressive load is evenly applied to the entire surface of the plate material while the third container is heated to the boiling point of methanol. Furthermore, each of the plate materials that constitute the upper and lower side surfaces of the third container is simultaneously translated toward the inside of the third container, and the upper and lower side surfaces of the group of hollow balls bonded by frictional heat are evenly compressed with a compressive stress equivalent to the compressive load applied to the plate material. Thereafter, the top of the third container is Each plate material constituting the lower side surface is returned to its original position; further, each plate material constituting the left and right side surfaces of the third container is simultaneously translated toward the inside of the third container, and the left and right side surfaces of the collection of hollow balls bonded by the frictional heat are uniformly compressed with a compressive stress equivalent to the compressive load applied to the plate materials; and then, each plate material constituting the left and right side surfaces of the third container is returned to its original position; by these processes, first, methanol is evaporated from the suspension prepared in the second step, and the collection of entangled aggregates is filled in all the gaps in the collection of hollow balls bonded by the frictional heat. a group of entangled aggregates precipitates, and the group of hollow balls joined by the frictional heat is covered with the group of entangled aggregates; the compressive stress is applied to the group of entangled aggregates covering the group of hollow balls joined by the frictional heat, and entanglement in the group of entangled aggregates progresses further; the compressive stress is applied to the group of entangled aggregates, and a portion of the group of entangled aggregates is forced into all gaps in the group of hollow balls joined by the frictional heat, and all of the gaps are filled with the group of entangled aggregates. the aggregates are filled with aggregates, the compressive stress is applied to the collection of entangled aggregates, contact portions between aggregates in the collection of entangled aggregates are joined by frictional heat, and the collection of entangled aggregates becomes a collection of aggregates joined by friction welding, the compressive stress is applied to the collection of aggregates joined by friction welding, and the collection of aggregates joined by friction welding is joined to the surfaces and sides of the collection of hollow balls joined by frictional heat, and as a result, the collection of hollow balls joined by frictional heat becomesA fourth step in which a sheet is formed that is covered with a collection of the friction welded aggregates; a fifth step of removing from the plate the weights that applied compressive stress to the plate in the fourth step, simultaneously applying the same impact acceleration to a plurality of locations on the reverse side of the bottom surface of the third container on which the sheet has been formed in the treatment in the fourth step, and peeling the sheet from the bottom surface of the third container, and simultaneously applying the same impact acceleration to a plurality of locations on the surface of the plate to which compressive stress has been applied in the fourth step, peeling the sheet from the plate, and removing the sheet; A method for performing all five of these steps consecutively is to produce a sheet in which a collection of hollow balls bonded by frictional heat is covered with a collection of carbon black aggregates bonded by friction welding.
[0008] By continuously carrying out all the treatments in the five steps described below, the collection of synthetic resin hollow balls bonded by frictional heat is covered with the collection of aggregates bonded by frictional welding. This gives the properties of the collection of aggregates bonded by frictional welding to the collection of synthetic resin hollow balls bonded by frictional heat. Here, the treatments in the five steps and the effects of the treatments will be described. In the first step, a group of hollow balls bonded by frictional heat is created. For this purpose, first, a group of synthetic resin hollow balls having the same shape and size is placed in a container having a bottom shape that is the same as the shape of the sheet to be created, and all of the group of hollow balls are brought into contact with each other at the skins of adjacent hollow balls, and the group of hollow balls is arranged in a plane as a group of hollow balls in one layer over the entire container. After this, a plate material that covers the entire group of hollow balls is placed on the group of hollow balls, and multiple weights are placed on the surface of the plate material at equal intervals. In other words, the volume of the air inside the hollow balls expands in response to the temperature difference due to the temperature rise, and when the volume expansion of the air exceeds a certain size, the state in which the group of hollow balls is arranged in a single layer in a plane collapses, and the group of hollow balls falls apart. For this reason, a compressive stress is applied to the group of hollow balls in the direction of gravity by the weight, and the state in which the group of hollow balls is arranged in a single layer in a plane is maintained. Note that synthetic resin hollow balls are produced by blow molding using thermoplastic resin pellets, but even if the blow molding conditions are the same, the outer diameter, skin thickness, and internal air volume of the produced hollow balls are not the same. For this reason, the description of a collection of hollow balls is not a collection of synthetic resin hollow balls of the same shape and size, but rather a collection of synthetic resin hollow balls of similar shape and size. In other words, according to Charles' law, the volume of the air inside the hollow ball expands by 1 / 273 of its volume at 0°C for every 1°C rise in temperature. Therefore, when the air inside the hollow ball rises by 20°C, its volume increases by 1.073 times, when the air inside the hollow ball rises by 50°C, its volume increases by 1.18 times, and when the air inside the hollow ball rises by 80°C, its volume increases by 1.29 times. In contrast, the thermal expansion coefficient of various synthetic resins is only 3-20×10 -5 / K. Therefore, when the hollow balls are heated, the thermal expansion of the air inside is significantly greater than the thermal expansion of the skin of the hollow balls. Therefore, when the group of hollow balls is heated, the thermal expansion of the air inside brings the skins of adjacent hollow balls into contact with each other. Furthermore, stresses in opposite directions act on the contact points of the skins of the adjacent hollow balls according to the temperature difference during heating. Therefore, the greater the temperature difference during heating, the greater the stress in the opposite directions. When the stress in the opposite directions reaches a certain level, the state in which the group of hollow balls is arranged in a flat layer is lost, and the group of hollow balls breaks apart. In order to avoid this phenomenon and firmly bond the skins of adjacent hollow balls to each other using frictional heat, a plate material that covers the entire group of hollow balls is placed on top of the group of hollow balls, and multiple weights are placed on the surface of the plate material at equal intervals, and the compression load of the weights holds the group of hollow balls in the direction of gravity, maintaining the state in which the group of hollow balls is arranged in a flat layer. Therefore, the compressive load applied by the weight is changed according to the temperature difference during heating. On the other hand, when the temperature difference during heating is increased, the thermal expansion of the hollow balls increases, which increases the contact area of the skins of adjacent hollow balls and also increases the frictional heat at the contact area. As a result, when the temperature difference during heating is increased, the joining force due to the frictional heat between adjacent hollow balls increases. However, as described above, the thermal expansion of the air due to the temperature difference during heating is large, so there is a limit to how much the compressive load of the weight can hold down the group of hollow balls in the direction of gravity. Therefore, the magnitude of the thermal expansion of the air due to the temperature difference during heating is determined by the volume of the hollow space in the hollow ball, so the temperature difference during heating and the magnitude of the compressive load applied by the weight are determined in advance based on experiments according to the volume of the hollow space in the hollow ball to be used. As a result, a group of hollow balls firmly bonded by frictional heat is formed. After that, the weight and the plate are removed, and the same impact acceleration of 0.2-0.3 G is simultaneously applied to multiple locations on the back surface of the bottom of the container depending on the size of the group of bonded hollow balls, and the group of hollow balls bonded by frictional heat is peeled off from the bottom of the container. In other words, the bonding force between the hollow balls due to frictional heat depends on the number of hollow balls whose skins are bonded to each other. In contrast, the bonding force between the bottom of the container and the group of hollow balls bonded by frictional heat depends on the number of hollow balls that come into contact with the bottom of the container. Since the number of the former is overwhelmingly greater than the number of the latter, when the same impact acceleration is simultaneously applied to multiple locations on the back surface of the bottom of the container, the group of hollow balls bonded by frictional heat is easily peeled off from the container. When the collection of hollow balls bonded by frictional heat returns to its original temperature, the air inside the hollow balls tries to return to its original volume. For this reason, when the skin of the hollow ball undergoes elastic deformation, the shape of the skin deviates slightly from a sphere, and the volume formed by the skin of the hollow ball decreases at a certain rate, the bonding force between the skins of adjacent hollow balls and the stress that tries to return the volume of the air inside the hollow ball to its original volume are balanced, and the collection of hollow balls bonded by frictional heat becomes stable. However, the inside of the hollow balls does not completely return to its original volume. In the second step, a suspension is prepared in which the entangled aggregates are dispersed in methanol. For this purpose, first, carbon black aggregates and methanol in an amount greater than the weight of the carbon black aggregates are put into a container, the methanol is stirred, and a suspension in which the carbon black aggregates are immersed in methanol is prepared. That is, by compressing the carbon black aggregates immersed in methanol, the carbon black aggregates can be easily crushed, and the crushed carbon black is dispersed in methanol, so that the carbon black aggregates are crushed by repeating the crushing of the carbon black aggregates. After this, a plate material that covers the entire surface of the suspension is placed on the suspension, and a compressive load is uniformly applied to the entire surface of the plate material to crush the carbon black aggregates immersed in methanol. Furthermore, the plate material is lifted from the suspension, and the container is placed on the vibration table of the vibrator, and the vibrator is operated to repeatedly apply acceleration in three directions, front-back, left-right, and up-down, each having a magnitude of 2-3G, to the container depending on the amount of carbon black, to rearrange the crushed carbon black aggregates in the methanol. That is, in the carbon black clusters, the size of the carbon black varies, and the size of the crushed carbon black also varies. Therefore, voids are formed in the crushed carbon black clusters. In order to fill these voids, the crushed carbon black clusters are rearranged and crushed again, so that the crushing of all the carbon black proceeds and the size of the crushed carbon black can be made closer to uniform. Furthermore, the plate material is covered with the suspension again, and the compressive load is applied uniformly again to the entire surface of the plate material, to further crush the carbon black clusters immersed in methanol. Furthermore, the plate material is lifted again from the suspension, and the acceleration in the three directions is applied again to the container. The pair of processes consisting of the process of applying the compressive load and the process of applying the acceleration are repeated, and when a repulsive force is generated in the plate material when the compressive load is applied to the plate material, it is determined that the crushing of the carbon black clusters immersed in methanol is completed, and the pair of processes is stopped. After this, the plate material is taken out of the first container.In other words, when the carbon black is crushed to a certain size, even if the crushed carbon black is compressed, no compressive stress is applied to the fine carbon black, so the fine carbon black is not crushed and a repulsive force is generated in the plate material. At this point, it is determined that the crushing of the carbon black clusters is complete. As a result, the carbon black is crushed to a size close to 1 / 25 of its original size. The smallest unit of carbon black is an aggregate, which is a primary agglomeration of carbon particles. In carbon black, this aggregate is a collection of carbon particles in which carbon particles with a size of 10-100 nm are linked together in an irregular and complex shape (called a structure). The size of the aggregate is 100-500 nm, and the number of carbon particles is 100-1000. Therefore, the aggregate is extremely light and can be cut. This aggregate is easily entangled by the structure, forming an agglomerate, which is a secondary agglomeration of carbon particles and an agglomerate of aggregates. Therefore, by crushing carbon black, the agglomerates are also crushed, and the size of the agglomerates is crushed to a size close to 1 / 25 of the original size. Furthermore, the aggregate is also cut to a length shorter than 0.2 mm. After this, a new suspension is created in which the entangled aggregates are dispersed in methanol. For this reason, the entanglement of the aggregates in the crushed carbon black is separated. That is, the aggregates are joined by friction welding at the contact sites where the aggregates contact each other, and the aggregates joined by friction welding are then joined by friction welding to the hollow balls joined by friction heat, so the entanglement of the aggregates in the crushed carbon black is once separated. Note that the entanglement of the aggregates is simply the contact of the aggregates with each other, and the bonding force between the aggregates in the entanglement is extremely small. In other words, carbon black is mostly composed of agglomerates, which are aggregate aggregates, and the larger ones are powders that reach nearly 1 mm in size. For this reason, it is difficult to create a suspension in which the agglomerates are dispersed in methanol, and it is even more difficult to bond the agglomerates to each other by friction welding. For this reason, a homogenizer is operated in methanol, shock waves are continuously applied to the crushed agglomerates, and the parts where the aggregates are directly entangled are separated by the irradiation of shock waves, methanol is adsorbed to the separated parts, and the aggregates are entangled through the methanol. Note that since the carbon black is crushed to the physically limiting size, the aggregates are cut to a length shorter than 0.2 mm. Therefore, by continuously applying shock waves, the entanglement between the aggregates can be easily released. As a result, the aggregates are entangled through the methanol, and by further continuously applying shock waves, a new suspension is formed in which the entangled aggregates are dispersed in low-viscosity methanol. For this reason, a homogenizer is placed in the container, the homogenizer is operated, and shock waves are repeatedly applied to the clusters of crushed carbon black through methanol. That is, when the homogenizer is operated in methanol, fine shock waves are continuously generated in the methanol, and the shock waves move through the methanol while exciting the methanol molecules. On the other hand, since the molecular weight of methanol is small and the viscosity is low, the methanol molecules are not easily excited by the shock waves, and the energy of the shock waves is not easily lost. For this reason, fine shock waves are efficiently and repeatedly irradiated through the methanol to the clusters of agglomerates immersed in the methanol. As a result, fine shock waves are repeatedly irradiated to the parts where the aggregates are directly entangled with each other, and since the aggregates are extremely light materials and the bonding strength between the entangled aggregates is weak, the parts where the direct entanglement is once released, and methanol is adsorbed to the parts of the aggregates where the entanglement is released. Furthermore, shock waves are repeatedly applied, and the clusters of aggregates entangled through the methanol are dispersed in the methanol. In addition, the aggregates have an irregular and complex structure in which carbon particles are strung together, and the size of each aggregate and the shape of the structure of each aggregate are different. Therefore, even if the shock waves generated by the homogenizer device are repeatedly irradiated to the agglomerates, all the parts where the aggregates are entangled in the aggregate collection are separated, and the aggregate collection is separated into individual aggregates, and the separated aggregates cannot be dispersed in methanol. In other words, the separation of the entanglement of the aggregates by the homogenizer device is a process of adsorbing methanol to the parts where the aggregates are entangled, and further dispersing the aggregate collection entangled through methanol in methanol. Therefore, in the aggregate collection in which the aggregates are entangled through methanol, the entangled aggregates are not joined to each other, and the aggregates entangled through methanol are dispersed in methanol. In addition, when an ultrasonic homogenizer is used as the homogenizer, a huge number of bubbles smaller than the size of the cut aggregates are generated at the same time, and then the bubbles disappear almost at the same time. The generation and disappearance of the bubbles occurs repeatedly according to the generation cycle of the ultrasonic waves, and the generation and disappearance of the bubbles are repeated in low-viscosity methanol (this phenomenon is called cavitation). Shock waves generated when the bubbles burst are continuously generated in low-viscosity methanol, and the shock waves are hardly absorbed and are continuously irradiated to the fine parts of the agglomerates, so that the parts where the aggregates are directly entangled with each other are separated in a short time, and methanol is adsorbed to the separated parts. Therefore, the ultrasonic homogenizer repeats the generation and disappearance of bubbles according to the generation cycle of the ultrasonic waves, so that the parts where the aggregates are directly entangled with each other can be separated in a short time. In the third step, all gaps in the group of hollow balls bonded by frictional heat are filled with a new suspension, the new suspension is interposed between the group of hollow balls bonded by frictional heat and the bottom surface of the third container, and the group of hollow balls bonded by frictional heat is immersed in the new suspension. For this purpose, a new container is prepared that is one size larger than the group of hollow balls bonded by frictional heat created in the first step, and that has a function in which each plate material constituting the four sides can move parallel to the inside of the container in a direction perpendicular to the side. After this, the group of hollow balls bonded by frictional heat is placed in the new container so that the same gaps are formed between the group of hollow balls and the four side surfaces. Furthermore, a part of the new suspension created in the second step is poured into the new container. Thereafter, a new container is placed on the vibration table of the vibration exciter used in the second step, the vibration exciter is operated, and vibration accelerations of 1-2 G in three directions (front-back, left-right, and up-down) are repeatedly applied to the new container depending on the weight of the collection of hollow balls joined by frictional heat, so that a new suspension is filled into all gaps in the collection of hollow balls joined by frictional heat, the new suspension is interposed between the collection of hollow balls joined by frictional heat and the bottom surface of the third container, and the collection of hollow balls joined by frictional heat is immersed in the new suspension. In the fourth step, the entire group of hollow balls joined by frictional heat is covered with a group of aggregates joined by frictional pressure welding. For this purpose, first, a plate material that covers the entire surface of the group of hollow balls joined by frictional heat immersed in a new suspension placed in the third container that has been treated in the third step is placed on the group of hollow balls joined by frictional heat immersed in the new suspension, and a compressive load is evenly applied to the entire surface of the plate material, while the third container is heated to the boiling point of methanol. Furthermore, each of the plate materials that constitute the upper and lower side surfaces of the new container are simultaneously translated inside the new container, and the upper and lower side surfaces of the group of hollow balls joined by frictional heat are evenly compressed with a compressive stress equivalent to the compressive load. After this, each of the plate materials that constitute the upper and lower side surfaces of the new container are returned to their original positions. Furthermore, each of the plate materials that constitute the left and right side surfaces of the new container are simultaneously translated inside the new container, and the left and right side surfaces of the group of hollow balls joined by frictional heat are evenly compressed with a compressive stress equivalent to the compressive load. Thereafter, the plate members constituting the left and right side surfaces of the new container are returned to their original positions. By these processes, first, methanol is evaporated from the new suspension prepared in the second step, and a collection of entangled aggregates is precipitated in all gaps in the collection of hollow balls bonded by frictional heat. In addition, the collection of hollow balls bonded by frictional heat is covered with a collection of entangled aggregates. Next, compressive stress is applied uniformly in sequence to the entire surface and side of the collection of hollow balls bonded by frictional heat, the collection of entangled aggregates is uniformly compressed, and the entanglement in the collection of entangled aggregates progresses further. Furthermore, compressive stress is applied uniformly to the collection of entangled aggregates, and a part of the collection of entangled aggregates is pushed into the gaps in the collection of hollow balls bonded by frictional heat. Further, compressive stress is applied uniformly, and all gaps are filled with the collection of entangled aggregates, and the entanglement in the collection of entangled aggregates progresses further, and there are no gaps in the collection of entangled aggregates. Further, compressive stress is applied evenly, and in the collection of entangled aggregates, the contact parts of the aggregates that are in contact with each other are joined by frictional heat, and the collection of entangled aggregates becomes a collection of aggregates joined by friction welding. Since each of the crushed aggregates has its own structure, the joining force between the aggregates in the collection of aggregates joined by friction welding is large. Further, compressive stress is applied evenly, and the collection of aggregates joined by friction welding is firmly joined by friction welding to the entire surface and side of the collection of hollow balls joined by frictional heat in order. In other words, the collection of aggregates joined by friction welding fills all the gaps in the collection of hollow balls joined by frictional heat, so the collection of aggregates joined by friction welding is firmly joined to the surface and side of the collection of hollow balls joined by frictional heat. As a result, a sheet is formed in which a group of hollow balls bonded by frictional heat is covered with a group of aggregates bonded by friction welding. In the fifth step, the sheet is removed. For this purpose, the weights that applied the compressive stress to the plate material in the fourth step are removed from the plate material. Furthermore, the same impact acceleration of 0.2-0.3G is simultaneously applied to the bottom surface of the new container on which the sheet is formed by the treatment in the fourth step at multiple locations on the back surface of the bottom surface, depending on the weight of the group of hollow balls bonded by frictional heat, and the sheet is peeled off from the new container. In other words, the bonding force between the bottom surface of the new container and the sheet depends on the number of hollow balls bonded to the new container through the group of aggregates bonded by frictional welding. In contrast, the bonding force between the group of hollow balls bonded by frictional heat and the group of aggregates bonded by frictional welding depends on the number of hollow balls that are bonded to adjacent hollow balls through the group of aggregates bonded by frictional welding. The former number is significantly smaller than the latter number. For this reason, when the same impact acceleration is simultaneously applied to multiple locations on the back surface of the bottom surface of the new container, the sheet is easily peeled off from the new container. Next, the same impact acceleration of 0.2-0.3G is simultaneously applied to multiple locations on the surface of the plate material to which the compressive stress was applied in the fourth step, depending on the weight of the group of hollow balls bonded by frictional heat, and the sheet is peeled off from the plate material. In other words, the bonding force between the plate material and the sheet depends on the number of hollow balls bonded to the plate material through the group of aggregates bonded by frictional welding. In contrast, the bonding force between the group of hollow balls bonded by frictional heat and the group of aggregates bonded by frictional welding depends on the number of hollow balls bonded to adjacent hollow balls through the group of aggregates bonded by frictional welding. The number of the former is significantly smaller than the number of the latter. Therefore, when the same impact acceleration is simultaneously applied to multiple locations on the surface of the plate material, the sheet is easily peeled off from the plate material. This allows the sheet to be taken out. The sheet thus produced exhibits the following effects. First, because the sheet is covered with a collection of aggregates bonded by friction welding, the sheet exhibits the excellent light blocking properties of carbon black, which has a total light transmittance of 0%. Therefore, the sheet will not deteriorate even if it is continuously exposed to ultraviolet rays. In addition, because carbon black has a high thermal emissivity of 0.95-0.97, the sheet acts as a heat dissipation sheet. Secondly, the aggregates bonded by friction welding form paths on the surface of the sheet through which electrons can move continuously, and as a result, the sheet has the electrical conductivity of carbon black, and based on this electrical conductivity, the sheet has electrical conductivity, electromagnetic shielding properties, and antistatic properties. Thirdly, the aggregates overlap each other without any gaps, and the aggregates are densely packed together and joined by friction welding. Therefore, the aggregates joined by friction welding have water repellency, which repels all liquids. In addition, carbon black does not react with acids or alkalis and is a chemically stable substance. Therefore, the sheet of the present invention has excellent chemical resistance compared to synthetic resin sheets. Fourth, when a group of aggregates joined by friction welding receives impact or shear force, the aggregate structure causes them to elastically deform, mitigating part of the impact or shear force. Also, a group of aggregates joined by friction welding has a certain tensile strength. Furthermore, when a group of hollow balls joined by frictional heat receives compressive stress, the internal air layer exerts a repulsive force against the compressive stress. Also, the skin of the hollow balls elastically deforms and absorbs part of the compressive stress. For this reason, the sheet has a certain compressive strength. Therefore, the sheet has a higher mechanical strength than a synthetic resin sheet made of the material of the hollow balls. Fifth, carbon black has higher heat resistance and flame resistance than synthetic resins. In other words, the ignition temperature of carbon black in the atmosphere exceeds 500°C. Therefore, the sheet has higher heat resistance and flame resistance than synthetic resin sheets. Sixth, a group of hollow balls bonded by frictional heat is significantly lighter than a synthetic resin molded body of the same size and thickness. Also, a group of aggregates bonded by friction welding fills the gaps between the group of hollow balls, but is significantly lighter than the group of hollow balls because its volume is significantly smaller than the volume occupied by the group of hollow balls. Therefore, a sheet that exerts the effects from the first to the fifth is lighter than a synthetic resin sheet of the same size and thickness. Seventh, the hollow balls made of synthetic resin are inexpensive industrial products, carbon black is an inexpensive industrial material, and methanol is the most widely used organic solvent. Furthermore, the sheet is made by continuously carrying out five steps consisting of extremely simple processing. Therefore, inexpensive sheets can be made using inexpensive raw materials and at low processing costs. Eighth, the sheets can be produced safely. In other words, the carbon black is soaked in methanol and processed as a suspension to produce the sheets, so the carbon black does not scatter as dust. In addition, the heat treatment temperature is the boiling point of methanol, which is more than 435°C lower than the ignition temperature of carbon black in the atmosphere, so the carbon black will not ignite. As described above, the sheet of the present invention not only solves all three of the problems described in paragraph 5, but also exhibits a variety of excellent effects and can be applied in a variety of fields.
[0009] The method for creating the sheet described in paragraph 7 is as follows: The synthetic resin hollow ball described in paragraph 7 is a hollow ball made of polyamide 66 resin, polyamide 6 resin, polyacetal resin, or polyetherimide resin, and the method of using the hollow ball as the synthetic resin hollow ball described in paragraph 7 and continuously carrying out all of the treatments in the five steps described in paragraph 7 is a method of producing a sheet in which a collection of synthetic resin hollow balls bonded by frictional heat is covered with a collection of carbon black aggregates bonded by friction welding.
[0010] Synthetic resin hollow balls are manufactured by blow molding of thermoplastic resin. On the other hand, polypropylene resin hollow balls were commercialized first as thermoplastic resin hollow balls, followed by polytetrafluoroethylene resin hollow balls, and more recently high-density polyethylene resin, polyvinyl chloride resin, polychlorinated vinyl chloride resin, and polyvinylidene fluoride resin hollow balls. These hollow balls are used in level gauges, oil baths, and thermostatic water baths to keep liquids warm and prevent evaporation and scattering, but their current use is limited to an extremely narrow purpose of floating hollow balls on the liquid surface. However, if a completely new function is found for hollow balls and the associated hollow balls exhibit a completely new function, hollow balls made of new materials according to the purpose will be commercialized. The hollow balls of the present invention are a collection of hollow balls arranged in a single layer on a flat surface, brought into contact with each other, and then heated to expand the volume of the air inside the hollow balls, and the skins of adjacent hollow balls are bonded together by frictional heat, which is a completely new way of using hollow balls. As a result, the collection of hollow balls bonded together by frictional heat becomes lighter than a synthetic resin sheet of the same size and thickness. Therefore, the higher the tensile strength of the thermoplastic resin and the higher the maximum elongation of the thermoplastic resin, the less likely the skin of the hollow ball will be destroyed even if the air inside the hollow ball expands in volume when the temperature is raised. Therefore, when hollow balls made of a thermoplastic resin with a high tensile strength and a high maximum elongation are used, the skin of the hollow ball is less likely to be destroyed even if the volume expansion of the air inside the hollow ball increases and the area of contact between the skins of adjacent hollow balls increases. As a result, the contact area between the skins of adjacent hollow balls increases, and the bonding strength at the contact points increases, making the bond between the skins of adjacent hollow balls less likely to be destroyed even when various loads are applied to the group of hollow balls. Here, the material, tensile strength, and maximum elongation of the thermoplastic resin constituting the hollow ball made of thermoplastic resin will be described. As described above, currently, hollow balls made of thermoplastic resin are made of the following thermoplastic resins: polypropylene resin, polytetrafluoroethylene resin, high-density polyethylene resin (also called hard polyethylene resin), polytetrafluoroethylene resin, polyvinyl chloride resin, polychlorinated vinyl chloride resin, and polyvinylidene fluoride resin. In contrast, although not currently commercialized, there are polyamide resin, polyacetal resin, and polyetherimide resin as thermoplastic resins that have high tensile strength, high maximum elongation, and are easy to blow mold. Note that thermosetting resins are hard resins that are difficult to deform, and therefore have low tensile strength and low maximum elongation. Next, the tensile strength and maximum elongation of thermoplastic resins will be described based on the description in Non-Patent Document 1. Polypropylene resin has a tensile strength of 35MPa and a maximum elongation of more than 500%. High density polyethylene resin has a tensile strength of 22-39MPa and a maximum elongation of 20-300%. Polytetrafluoroethylene resin has a tensile strength of 14-35MPa and a maximum elongation of 200-400%. Polyvinyl chloride resin has a tensile strength of 44-59MPa and a maximum elongation of 50-150%. Polychlorinated vinyl chloride resin has a tensile strength of 52-59MPa and a maximum elongation of 80-120%. Polyvinylidene fluoride resin has a tensile strength of 36-57MPa and a maximum elongation of 100-300%. In contrast, polyamide 66 resin has a tensile strength of 77-84 MPa and a maximum elongation of 60-300%. Polyamide 6 resin has a tensile strength of 70-83 MPa and a maximum elongation of 200-300%. Polyacetal resin has a tensile strength of 70 MPa and a maximum elongation of 25-75%. Polyetherimide resin has a high tensile strength of 105 MPa and a maximum elongation of 60%. These four types of thermoplastic resin have both higher tensile strength and higher maximum elongation than the thermoplastic resins that have been used for hollow balls to date, and have both higher tensile strength and higher maximum elongation than any other thermoplastic resin. Therefore, hollow balls made of these four types of thermoplastic resins have high tensile strength and large maximum elongation, so even if the temperature difference during heating is increased, the volume expansion of the air in the hollow ball is increased, and the area of contact between the skins of the hollow balls is increased, the skin of the hollow ball is not easily broken because the tensile strength of the skin of the hollow ball is high and the maximum elongation is large. As a result, the bonding force between adjacent hollow balls is increased. For this reason, even if various loads are applied to a collection of hollow balls bonded by frictional heat, the bonds between the hollow balls are not easily broken, making these thermoplastic resins suitable for use as thermoplastic resins for making hollow balls.
[0011] The method for creating the sheet described in paragraph 7 is as follows: The carbon black described in paragraph 7 is acetylene black, and a method of using the acetylene black as the carbon black described in paragraph 7 and continuously carrying out all of the five steps described in paragraph 7 is a method of producing a sheet in which a collection of hollow balls of synthetic resin bonded by frictional heat is covered with a collection of acetylene black aggregates bonded by friction welding.
[0012] In other words, the characteristics of carbon black vary greatly depending on the manufacturing method, and carbon black is classified according to the name of the manufacturing method. The properties of carbon black vary depending on the manufacturing method. Furnace black is carbon black produced by incomplete combustion of oil or gas in high-temperature gas, and is subdivided into oil furnaces and gas furnaces depending on the raw material burned. Among furnace blacks, Ketjen black uses oil made of hydrocarbons as the raw material, and produces carbon black by incomplete combustion of the oil. Among carbon blacks, Ketjen black has the largest specific surface area and DPB (dibutyl phthalate) absorption, and its electrical conductivity is second only to acetylene black. In other words, Ketjen black has a hollow body formed by the structure of an arc, and the electrical conductivity of Ketjen black increases as electrons move through the arc-shaped structure. Other types of carbon black include channel black, which is made by burning natural gas and scraping off the deposits that form on channel steel; acetylene black, which is obtained by pyrolyzing acetylene gas; and thermal black, which is produced by repeatedly burning and decomposing gas in a heat-storing furnace. Acetylene black is produced using acetylene gas, which has the highest purity among the raw materials for carbon black, and therefore has the fewest impurities among carbon blacks, and also has the most developed structure and primary particles. For this reason, it has the highest electrical conductivity among carbon blacks. Therefore, a sheet consisting of a collection of acetylene black aggregates bonded by friction welding and covering a collection of synthetic resin hollow balls bonded by friction heat has better electrical conductivity than sheets using other carbon blacks. Also, since the structure and primary particles are the most developed, acetylene black aggregates are easily entangled, and once entangled, the aggregates are difficult to separate. Therefore, the mechanical strength of the collection of acetylene black aggregates bonded by friction welding is higher than that of the collection of aggregates using other carbon blacks. For this reason, acetylene black is suitable as the carbon black constituting the sheet described in paragraph 7. Acetylene black, for example, has a bulk density of 0.04 g / cm 3 There is a powder product available with an electrical resistivity of 0.21 Ω·cm. In addition, in the aggregate assembly in which all the aggregates are friction-welded, all the aggregates are connected to each other, so that a path for electrons to move is formed in the aggregate assembly, and the sheet has the electrical conductivity of acetylene black.
[0013] The method for creating the sheet described in paragraph 7 is as follows: The carbon black described in paragraph 7 is Ketjen black, and a method of using the Ketjen black as the carbon black described in paragraph 7 and continuously carrying out all of the treatments in the five steps described in paragraph 7 is a method of producing a sheet in which a collection of hollow balls of synthetic resin bonded by frictional heat is covered with a collection of Ketjen black aggregates bonded by friction welding.
[0014] In other words, among carbon blacks, Ketjenblack has the smallest primary particles, the largest number of primary particles per unit mass, and the largest BET surface area, and therefore has the best light-blocking properties among all carbon blacks. For this reason, sheets using Ketjenblack as the carbon black have better light-blocking properties than sheets using other carbon blacks. Furthermore, Ketjenblack has the highest thermal emissivity of 0.97, and sheets using Ketjenblack as the carbon black have better heat dissipation properties than sheets using other carbon blacks. That is, Ketjen Black has a primary particle diameter of 30-40 nm, and the number of primary particles per unit mass is 1×10 7 / g and a BET surface area of 1270m 2 Therefore, a sheet consisting of a group of Ketjen black aggregates bonded by friction welding covering a group of synthetic resin hollow balls bonded by frictional heat has better light blocking and heat dissipation properties than sheets using other carbon blacks.
[0015] The method of bonding the sheet prepared by the method described in paragraph 7 to the surface of a substrate or part is as follows: The sheet prepared by the method described in paragraph 7 is placed on the surface of a substrate or a component, and a compressive stress is applied uniformly to the entire surface of the sheet, whereby first, a group of friction-welded aggregates covering the surface of the sheet contacts the surface of the substrate or the component, and then, the compressive stress is applied to the group of friction-welded aggregates, and a part of the group of friction-welded aggregates that contacts the surface of the substrate or the component elastically deforms, and the elastically deformed friction-welded aggregates are deformed. 8. A method of bonding a sheet prepared by the method described in paragraph 7 to a surface of a substrate or a component, wherein a portion of a group of gates penetrates into a recess in the uneven surface of the substrate or the component and fills the recess in the surface, and further wherein the compressive stress is applied to the group of aggregates joined by the friction welding, generating frictional heat at a contact portion where the group of aggregates joined by the friction welding comes into contact with the surface of the substrate or the component, and the frictional heat bonds the group of aggregates joined by the friction welding to the surface of the substrate or the component.
[0016] That is, the sheet prepared by the method described in paragraph 7 is placed at a predetermined position on the surface of the substrate or part, and compressive stress is applied evenly to the entire surface of the sheet. First, the friction-welded aggregate assembly covering the surface of the sheet comes into contact with the surface of the substrate or part. Next, a part of the friction-welded aggregate assembly that comes into contact with the surface of the substrate or part is elastically deformed, and a part of the elastically deformed friction-welded aggregate assembly enters the concave portion of the uneven surface of the substrate or part and fills the concave portion of the surface. This eliminates gaps at the contact portion where the friction-welded aggregate assembly comes into contact with the surface of the substrate or part. Furthermore, when compressive stress is applied, frictional heat is generated at the contact portion where the friction-welded aggregate assembly comes into contact with the surface of the substrate or part, since there is already no gap at the contact portion. This frictional heat bonds the friction-welded aggregate assembly covering the surface of the sheet to the surface of the substrate or part. That is, the unevenness of the surface of the substrate or part is small, at submicrons, but the number of protrusions that come into contact with the surface of the sheet is enormous. Therefore, when the surface of the sheet placed on the surface of the substrate or part is compressed evenly, the following phenomena occur in succession. First, the aggregates bonded by friction welding come into contact with the surface of the substrate or part. Next, a part of the contact part of the aggregates bonded by friction welding undergoes slight elastic deformation, and a part of the elastically deformed contact part enters the concave part of the unevenness of the surface of the substrate or part and fills the concave part of the surface. As a result, there is no gap at the contact part where the aggregates bonded by friction welding come into contact with the surface of the substrate or part. Furthermore, when compressive stress is applied, frictional heat is generated at the contact part where the aggregates bonded by friction welding come into contact with the surface of the substrate or part, since there is already no gap at the contact part. This frictional heat causes the aggregates bonded by friction welding to bond to the unevenness of the surface of the substrate or part. On the other hand, the number of projections and recesses at the contact points on the surface of the substrate or part is enormous, and the distance between the projections and recesses is very short. Therefore, the aggregates joined by friction welding are firmly bonded to the surface of the substrate or part. On the other hand, the aggregates joined by friction welding are firmly bonded to the hollow balls joined by friction heat. This allows the sheet to be firmly bonded to the surface of the substrate or part. The frictional heat generated at the contact area occurs instantaneously and then cools down in a short time. Therefore, even if the substrate or part is made of a synthetic resin with low heat resistance, or a cloth or nonwoven fabric, the sheet will bond to the surface of the substrate or part. Therefore, the sheet can be bonded to substrates or parts made of various materials by the extremely simple means of friction welding. As a result, the various properties of the sheet described in paragraph 7 are imparted to the surfaces of substrates or parts made of various materials. [Brief description of the drawings]
[0017] [Figure 1]This is a schematic diagram showing an enlarged portion of the fracture surface structure of a sheet in which the surface of the sheet is evenly covered with aggregates and all gaps between the hollow balls are filled with aggregates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Example 1 In this embodiment, a group of hollow balls made of polyamide 66 resin are bonded by frictional heat between the skins of adjacent hollow balls. The material of the hollow balls is not limited to polyamide 66 resin. As described in paragraph 10, in addition to polyamide 66 resin, polyamide 6 resin, polyacetal resin, and polyetherimide resin are also available as thermoplastic resins with high tensile strength and high maximum elongation. By using hollow balls made of these thermoplastic resins, the bonding strength between the skins of adjacent hollow balls is increased. The hollow ball used, made of polyamide 66 resin, has an outer diameter of 3 cm, a skin thickness of 0.75 cm, and the shape of the internal air layer is similar to that of a sphere with a diameter of 1.5 cm (prototype by Plaki Kogyo Co., Ltd.). The above-mentioned collection of hollow balls was placed in a container with a bottom shape of 30 cm x 30 cm, and all the hollow balls were arranged in a flat manner as a collection of hollow balls in one layer over the entire container, with the skins of adjacent hollow balls in contact with each other. Next, a plate material that covers the entire collection of hollow balls was placed on top of the collection of hollow balls, and 13 weights of 1 kg were placed on the surface of the plate material at approximately equal intervals. After this, the container was heated from 20°C to 60°C. As a result, the volume of the air in the hollow balls increased by 1.15 times. Furthermore, the weights and the plate material were removed, and an impact acceleration of 0.2 G was simultaneously applied to 13 points on the back surface of the bottom of the container, and the collection of hollow balls bonded by frictional heat was peeled off from the container and the collection of hollow balls bonded by frictional heat was taken out.
[0019] Example 2 In this example, acetylene black is used as carbon black, and the acetylene black is crushed in methanol to a limited size. The crushed acetylene black is then dispersed in methanol to form a suspension 1, in which aggregates of acetylene black entangled with each other are dispersed. First, 10 g of acetylene black (Li-100, a product of Denka Co., Ltd.) and 80 g of industrial grade 1 methanol were filled into a container, and the excess methanol was stirred to immerse the acetylene black in the methanol. The acetylene black used had an average particle size of 35 nm and a specific surface area of 68 m 2 / g and is composed of primary particles with an iodine adsorption capacity of 92mg / g. Acetylene black also has a bulk density of 0.04g / ml and an electrical resistivity of 0.21Ω·cm, making it the most conductive of all carbon blacks. After this, a flat plate was placed on the container, and nine 2 kg weights were placed on the plate at approximately equal intervals. The weights and the flat plate were then removed, and the container was fixed on a vibration table, and a vibration acceleration of 2 G was repeatedly applied to the container in three directions: front-back, left-right, and up-down. After repeating this pair of processes of applying a compressive load and applying a vibration acceleration five times, the weight was placed on the flat plate, but since there was no movement of the flat plate at all, it was determined that the acetylene black had been crushed to the limit size in methanol, and the pair of processes was stopped. Furthermore, an ultrasonic homogenizer (LUH150, product of Yamato Scientific Co., Ltd.) was operated in the methanol in the container to apply an ultrasonic signal of 20 kHz for 15 minutes, thereby creating suspension 1 in which a collection of entangled aggregates of acetylene black was dispersed in methanol via the methanol.
[0020] Example 3 In this example, Ketjen black is used as carbon black, and the Ketjen black is crushed in methanol to a minimum size. The crushed Ketjen black is then dispersed in methanol to form a suspension 2 in which aggregates formed by entanglement of Ketjen black aggregates are dispersed in methanol. First, 10 g of Ketjen Black (EC600JD, a product of Lion Corporation) and 80 g of industrial grade 1 methanol were filled into a container, and the excess methanol was stirred to immerse the Ketjen Black in the methanol. The Ketjen Black used had a small average particle size of 34 nm and a specific surface area of 1270 m2. 2 / g, which shows excellent light-shielding properties. Furthermore, the amount of dibutyl phthalate required to fill the gaps between Ketjen Black particles is 495 cm 3 / 100g, the degree of particle connection and particle aggregation is large. This promotes the entanglement of Ketjen Black aggregates, resulting in excellent light blocking properties. After this, a flat plate was placed on the container, and nine 2 kg weights were placed on the plate at approximately equal intervals. The weights and the flat plate were then removed, and the container was fixed on a vibration table, and a vibration acceleration of 2 G was repeatedly applied to the container in three directions: front-back, left-right, and up-down. After repeating this pair of processes of applying a compressive load and applying a vibration acceleration five times, the weight was placed on the flat plate, but since there was no movement of the flat plate at all, it was determined that the Ketjen Black had been crushed to the limit size in methanol, and the pair of processes was stopped. Furthermore, an ultrasonic homogenizer (LUH150, product of Yamato Scientific Co., Ltd.) was operated in the methanol in the container, and a 20 kHz ultrasonic signal was applied for 15 minutes to create suspension 2 in which a collection of entangled Ketjen Black aggregates was dispersed in methanol via the methanol.
[0021] Example 4 In this example, all gaps in the collection of hollow balls joined by frictional heat produced in Example 1 are filled with the suspension 1 produced in Example 2, suspension 1 is interposed between the collection of hollow balls joined by frictional heat and the bottom surface of a container, and further, the collection of hollow balls joined by frictional heat is immersed in the suspension 1 to a thickness less than 1 mm. Similarly, all gaps in the collection of hollow balls joined by frictional heat prepared in Example 1 are filled with the suspension 2 prepared in Example 3, and the suspension 2 is interposed between the collection of hollow balls joined by frictional heat and the bottom surface of a container. Furthermore, the collection of hollow balls joined by frictional heat is immersed in the suspension 2 to a thickness less than 1 mm. For this purpose, a container was first prepared with an outer dimension of 34.5 cm x 34.5 cm, a depth of 2 cm, and a width of 2 cm, and with a function that each plate constituting the four sides can move parallel to the inside of the container in a direction perpendicular to the sides. Next, the collection of hollow balls bonded by frictional heat prepared in Example 1 was placed 0.5 cm away from the four sides of the container. Furthermore, 5 g of the suspension 1 prepared in Example 2 was poured into the container, and the collection of hollow balls bonded by frictional heat was immersed in the suspension 1. Similarly, a container was prepared with an outer dimension of 34.5 cm x 34.5 cm, a depth of 2 cm, and a width of 2 cm, and in which each plate constituting the four sides could move in parallel in a direction perpendicular to the sides toward the inside of the container. Next, the collection of hollow balls bonded by frictional heat prepared in Example 1 was placed 0.5 cm away from the four sides of the container. Furthermore, 5 g of the suspension 2 prepared in Example 3 was poured into the container, and the collection of hollow balls bonded by frictional heat was immersed in the suspension 2. After this, each container was placed in order on the vibration table of the vibration exciter used in Example 2, and the vibration exciter was operated to repeatedly apply a vibration acceleration of 2G in three directions: front-back, left-right, and up-down, to each container.
[0022] Example 5 In this embodiment, two types of sheets are produced: one in which a collection of hollow balls joined by frictional heat is entirely covered with a collection of acetylene black aggregates joined by friction welding, and the other in which a collection of Ketjen black aggregates joined by friction welding is entirely covered. For this reason, a plate material covering the entire hollow ball group was placed on the group of hollow balls immersed in the suspension 1 in Example 4 and bonded by frictional heat, and 13 weights of 1 kg were placed on the surface of the plate material at approximately equal intervals, and the container was heated to the boiling point of methanol. After that, each of the plate materials constituting the upper and lower side surfaces of the container was moved in parallel to the inside of the container at the same time, and the upper and lower side surfaces of the group of hollow balls bonded by frictional heat were compressed evenly with a compressive stress equivalent to the above-mentioned compressive load, and then each of the plate materials constituting the upper and lower side surfaces of the container was returned to its original position. Furthermore, each of the plate materials constituting the left and right side surfaces of the container was moved in parallel to the inside of the container at the same time, and the left and right side surfaces of the group of hollow balls bonded by frictional heat were compressed evenly with a compressive stress equivalent to the above-mentioned compressive load, and then each of the plate materials constituting the left and right side surfaces of the container was returned to its original position. This produced a sheet 1 in which a collection of hollow balls bonded by frictional heat was covered with a collection of acetylene black aggregates bonded by friction welding. Similarly, for the group of hollow balls immersed in suspension 2 in Example 4 and bonded by frictional heat, a plate material covering the entire group of hollow balls was placed on the group of hollow balls, 13 weights of 1 kg were placed on the surface of the plate material at approximately equal intervals, and the container was heated to the boiling point of methanol. After that, each of the plate materials constituting the upper and lower side surfaces of the container was moved in parallel to the inside of the container at the same time, and the upper and lower side surfaces of the group of hollow balls bonded by frictional heat were compressed evenly with a compressive stress equivalent to the above-mentioned compressive load, and then each of the plate materials constituting the upper and lower side surfaces of the container was returned to its original position. Furthermore, each of the plate materials constituting the left and right side surfaces of the container was moved in parallel to the inside of the container at the same time, and the left and right side surfaces of the group of hollow balls bonded by frictional heat were compressed evenly with a compressive stress equivalent to the above-mentioned compressive load, and then each of the plate materials constituting the left and right side surfaces of the container was returned to its original position. This produced sheet 2 in which a collection of hollow balls bonded by frictional heat was covered with a collection of Ketjen Black aggregates bonded by friction welding.
[0023] Example 6 In this example, each of the two types of sheets prepared in Example 5 was peeled off from the bottom surface of the container, and further peeled off from the plate material to which compressive stress had been applied, and the two types of sheets were taken out. First, the 13 weights were removed from the plate. Then, an impact acceleration of 0.2G was simultaneously applied to 13 points on the back surface of the bottom of the container, and each sheet was peeled off from the container. Furthermore, an impact acceleration of 0.2G was simultaneously applied to 13 points on the front surface of the plate, and each sheet was peeled off from the plate, and two types of sheets were taken out.
[0024] Example 7 In this example, the properties of each of the two types of sheets prepared in Example 6 were evaluated, and the structures of the surfaces and fracture surfaces of the two types of sheets were examined by electron microscope. First, the surface resistance of multiple points on the surface of Sheet 1 was measured using a surface resistance meter (for example, a surface resistance meter ST-4 from SIMCO Japan Co., Ltd.). Since the surface resistivity was 1.0 Ω, the sheet had a resistance close to the resistivity of acetylene black, which is 0.21 Ω cm. Therefore, based on the resistivity of acetylene black, Sheet 1 has the functions of conductivity, electromagnetic shielding, and antistatic properties. Next, the light-shielding property of Sheet 1 was measured based on the JIS-L-1055A method, and it was found to have a light-shielding rate of 95%, making it an excellent light-shielding sheet. Therefore, the sheet 1 functions as a sheet with excellent electrical conductivity and light-shielding properties due to the electrical conductivity and light-shielding properties of acetylene black. Furthermore, the light-shielding property of Sheet 2 was measured based on the JIS-L-1055A method, and it was found to have a light-shielding rate of 96%, making it an excellent light-shielding sheet. Next, the thermal emissivity of Sheet 2 was measured using an analyzer consisting of a Fourier transform infrared spectrophotometer and a radiation measurement unit (equipment owned by Kobelco Research Institute, Inc.), and it was found to have a high thermal emissivity of 0.94, making it an excellent heat dissipation sheet. Therefore, Sheet 2 acts as a sheet with excellent light blocking and heat dissipation properties based on the light blocking and heat dissipation properties of Ketjen Black. Furthermore, diethyl ether (CH3CH2)2O was sprayed onto the surfaces of Sheet 1 and Sheet 2, but the diethyl ether was repelled from the surfaces of the sheets. Note that diethyl ether has a surface tension of 17.01 dyn / cm at 20°C, making it the smallest surface tension of all liquids. Incidentally, the surface tension of water is 72.75 dyn / cm at 20°C. For this reason, the surfaces of the sheets are water-repellent and repel all liquids. Furthermore, Sheet 1 and Sheet 2 were allowed to drop from a height of 2 m five times without any damage. Therefore, the mechanical strength of the sheet is higher than that of a molded body made of polyamide 66 resin with a thickness of 3 mm. Next, the structure and constituent materials of the surfaces and fracture surfaces of Sheets 1 and 2 were examined using an electron microscope. An extremely low accelerating voltage SEM owned by JFE Techno-Research Corporation was used as the electron microscope. This device allows surface observation at extremely low accelerating voltages starting from 100V, and further allows the surface of the sample to be observed directly without forming a conductive coating. Secondary electron beams between 900-1000 volts were extracted from the electron beams reflected from the surfaces of Sheet 1 and Sheet 2 and image processing was performed. Fine black matter was layered with no gaps and highly integrated. Next, energy between 900-1000 volts was extracted from the electron beams reflected from the surfaces and image processing was performed, and the material of the black matter was analyzed based on the shade of the image. Since no shade was observed, it was found to be composed of a single atom. Furthermore, the energy and intensity of the characteristic X-rays from the surface were image processed and the type of elements that make up the black matter was analyzed. The black matter was composed only of carbon atoms. From the above observation results, it was found that aggregates of acetylene black or aggregates of ketjen black were layered over the entire surface of the sheets. Next, sheets 1 and 2 were cut and the cut surfaces were observed under an electron microscope. A secondary electron beam between 900-1000 volts was extracted from the reflected electron beam from the cut surfaces and image processing was performed. In sheets 1 and 2, a collection of aggregates that overlapped with no gaps and accumulated at high density covered the entire surface of the hollow ball and filled all the gaps in the hollow ball. Figure 1 shows a schematic enlarged view of the cut surface. 1 is a collection of acetylene black or ketjen black aggregates joined by friction welding, and 2 is a hollow ball made of polyamide 66 resin. As explained above, the sheet of the present invention exhibited the effects of the sheet described in paragraph 8. First, the sheet had excellent light blocking properties based on the total light transmittance of carbon black. Second, the sheet had electrical conductivity based on the electrical conductivity of acetylene black. Third, the sheet had excellent heat dissipation properties based on the thermal emissivity of Ketjen black. Fourth, the surface of the sheet had water repellency that repelled all liquids. Fourth, the sheet had higher mechanical strength than a molded body made of polyamide 66 resin with a thickness of 3 mm.
[0025] Example 8 In this example, the sheet 2 prepared in Example 6 is frictionally welded to a sheet made of polyamide 66 resin. First, two flat plates each having a size of 32 cm x 32 cm x 1 cm (thickness) are prepared. Next, a polyamide 66 resin sheet having a size of 30 cm x 30 cm x 1 mm (thickness) is molded. Furthermore, the polyamide 66 resin sheet and the sheet 2 prepared in Example 6 are stacked in order on one flat plate, and then another flat plate is stacked on top of the sheet, and 13 weights of 10 kg are placed at approximately equal intervals. After this, the weights are removed. Furthermore, a vertical impact acceleration of 0.2 G is simultaneously applied to nine places on the bottom surface of the lower flat plate, and the bonded body of the polyamide 66 resin sheet and the sheet 2 is peeled off from the flat plate. Furthermore, a vertical impact acceleration of 0.2 G is simultaneously applied to nine places on the bottom surface of the upper flat plate, and the bonded body of the polyamide 66 resin sheet and the sheet 2 is peeled off from the flat plate. That is, as described in paragraph 16, the bonding strength between the group of aggregates bonded by friction welding and the surface of the substrate or part is large. Therefore, the bonding strength between the lower plate and the polyamide 66 resin sheet is smaller than the bonding strength between the polyamide 66 resin sheet and Sheet 2. Also, the bonding strength between the upper plate and Sheet 2 is smaller than the bonding strength between the polyamide 66 resin sheet and Sheet 2. As a result, a sheet was created in which the polyamide 66 resin sheet and Sheet 2 were integrated. In this way, the polyamide 66 resin sheet is integrated with sheet 2, thereby reinforcing the polyamide 66 resin sheet. The light-blocking and heat-dissipating properties of Ketjen black are imparted to the polyamide 66 resin sheet. Furthermore, the water-repellent properties that repel all liquids are imparted to the polyamide 66 resin sheet. Incidentally, by integrating sheet 1 with the polyamide 66 resin sheet, the electrical conductivity and light-blocking properties of acetylene black are imparted to the polyamide 66 resin sheet. The object to which the sheet 1 or sheet 2 is frictionally welded is not limited to a synthetic resin sheet. By frictionally welding the sheet 1 or sheet 2 to a base fabric made of synthetic resin fibers or a nonwoven fabric made of synthetic resin fibers, the properties of Ketjen black or acetylene black are imparted to the base fabric or nonwoven fabric. [Explanation of symbols]
[0026] 1. Aggregates of acetylene black or ketjen black joined by friction welding. 2. Hollow ball made of polyamide 66 resin.
Claims
1. The method for producing a sheet in which a group of synthetic resin hollow balls bonded by frictional heat are covered with a group of carbon black aggregates bonded by friction welding is as follows: A collection of synthetic resin hollow balls of the same shape and size is placed in a first container having a bottom shape that is the same as the shape of the sheet to be produced, and the skins of all of the hollow balls are brought into contact with each other in the collection of hollow balls, and the collection of hollow balls is arranged in a plane as a collection of hollow balls in a single layer throughout the first container. Thereafter, a plate material that covers the entire collection of hollow balls is placed on top of the collection of hollow balls, and multiple weights are placed at equal intervals on the surface of the plate material to uniformly compress the collection of hollow balls. a first step of heating the first container to a predetermined temperature, whereby the air inside the hollow balls thermally expands, causing the skins of adjacent hollow balls to come into contact with each other and generating frictional heat at the contact points, and the contact points are bonded together by the frictional heat to form a group of hollow balls bonded together by the frictional heat; thereafter, removing the weight and the plate material; and further, simultaneously applying the same impact acceleration to multiple locations on the reverse side of the bottom surface of the first container to peel off the group of hollow balls bonded together by the frictional heat from the bottom surface of the first container, and removing the group of hollow balls bonded together by the frictional heat; A carbon black cluster and methanol in an amount greater than the weight of the carbon black cluster are placed in a second container, the methanol is stirred, and the carbon black clusters are immersed in the methanol. Thereafter, a plate material covering the entire surface of the carbon black clusters is placed on the carbon black clusters, and a compressive load is applied evenly to the entire surface of the plate material to crush the carbon black clusters immersed in the methanol. The second container is placed on a vibration table of a vibrator, the vibrator is operated, and vibration accelerations in three directions, front-back, left-right, and up-down, are repeatedly applied to the second container to rearrange the crushed carbon black clusters in the methanol. Thereafter, the plate material is placed on the carbon black clusters again, and the compressive load is applied evenly to the entire surface of the plate material again to further crush the crushed carbon black clusters in the methanol. a second step of repeatedly applying the vibration acceleration in the three directions to the second container, repeating a pair of steps consisting of the step of applying the compressive load and the step of applying the vibration acceleration, and judging that the crushing of the carbon black clumps in the methanol is completed when a repulsive force is generated in the plate material when the compressive load is applied to the plate material, and stopping the pair of steps, and then removing the plate material from the second container, and a second step of disposing a homogenizer device in the second container and operating the homogenizer device to repeatedly apply shock waves via the methanol to the crushed carbon black clumps, thereby separating the entanglements between aggregates in the crushed carbon black, entangling the aggregates with each other via the methanol, and preparing a suspension in which the entangled aggregate clumps are dispersed in methanol; a third process in which the collection of hollow balls joined by frictional heat produced in the first process is placed in a third container having a bottom larger than the collection of hollow balls joined by frictional heat and each of the plate materials constituting the four side surfaces has a function of moving parallel to the inside of the container in a direction perpendicular to the side surfaces, so that a gap of the same size is formed between the collection of hollow balls joined by frictional heat and the four side surfaces; further, a part of the suspension produced in the second process is poured into the third container to immerse the collection of hollow balls joined by frictional heat in the suspension; thereafter, the third container is placed on the vibration table of the vibration exciter used in the second process, the vibration exciter is operated, and vibration accelerations in three directions, front-back, left-right, and up-down, are repeatedly applied to the third container; thereby, the suspension is filled in all gaps in the collection of hollow balls joined by frictional heat, and the suspension is interposed between the collection of hollow balls joined by frictional heat and the bottom surface of the third container; and further, the collection of hollow balls joined by frictional heat is immersed in the suspension; A plate material that covers the entire surface of the group of hollow balls bonded by frictional heat placed in the third container that has completed the treatment in the third step is placed on the group of hollow balls bonded by frictional heat, and a compressive load is evenly applied to the entire surface of the plate material while the third container is heated to the boiling point of methanol. Furthermore, each of the plate materials that constitute the upper and lower side surfaces of the third container is simultaneously translated toward the inside of the third container, and the upper and lower side surfaces of the group of hollow balls bonded by frictional heat are evenly compressed with a compressive stress equivalent to the compressive load applied to the plate material. Thereafter, the top of the third container is Each plate material constituting the lower side surface is returned to its original position; further, each plate material constituting the left and right side surfaces of the third container is simultaneously translated toward the inside of the third container, and the left and right side surfaces of the collection of hollow balls bonded by the frictional heat are uniformly compressed with a compressive stress equivalent to the compressive load applied to the plate materials; and then, each plate material constituting the left and right side surfaces of the third container is returned to its original position; by these processes, first, methanol is evaporated from the suspension prepared in the second step, and the collection of entangled aggregates is filled in all the gaps in the collection of hollow balls bonded by the frictional heat. a group of entangled aggregates precipitates, and the group of hollow balls joined by the frictional heat is covered with the group of entangled aggregates; the compressive stress is applied to the group of entangled aggregates covering the group of hollow balls joined by the frictional heat, and entanglement in the group of entangled aggregates progresses further; the compressive stress is applied to the group of entangled aggregates, and a portion of the group of entangled aggregates is forced into all gaps in the group of hollow balls joined by the frictional heat, and all of the gaps are filled with the group of entangled aggregates. the aggregates are filled with aggregates, the compressive stress is applied to the collection of entangled aggregates, contact portions between aggregates in the collection of entangled aggregates are joined by frictional heat, and the collection of entangled aggregates becomes a collection of aggregates joined by friction welding, the compressive stress is applied to the collection of aggregates joined by friction welding, and the collection of aggregates joined by friction welding is joined to the surfaces and sides of the collection of hollow balls joined by frictional heat, and as a result, the collection of hollow balls joined by frictional heat becomesA fourth step in which a sheet is formed that is covered with a collection of the friction welded aggregates; a fifth step of removing from the plate the weights that applied compressive stress to the plate in the fourth step, simultaneously applying the same impact acceleration to a plurality of locations on the reverse side of the bottom surface of the third container on which the sheet has been formed in the treatment in the fourth step, and peeling the sheet from the bottom surface of the third container, and simultaneously applying the same impact acceleration to a plurality of locations on the surface of the plate to which compressive stress has been applied in the fourth step, peeling the sheet from the plate, and removing the sheet; A method in which all of these five steps are carried out consecutively is a method for producing a sheet in which a collection of hollow balls bonded by frictional heat is covered with a collection of carbon black aggregates bonded by friction welding.
2. The method for producing the sheet according to claim 1 comprises the steps of: The synthetic resin hollow ball recited in claim 1 is a hollow ball made of polyamide 66 resin, polyamide 6 resin, polyacetal resin, or polyetherimide resin, and the method of using the hollow ball as the synthetic resin hollow ball recited in claim 1 and continuously carrying out all of the five steps recited in claim 1 is a method of producing a sheet in which a collection of synthetic resin hollow balls bonded by frictional heat is covered with a collection of carbon black aggregates bonded by friction welding.
3. The method for producing the sheet according to claim 1 comprises the steps of: The carbon black recited in claim 1 is acetylene black, and the method of using the acetylene black as the carbon black recited in claim 1 and continuously carrying out all of the five steps recited in claim 1 is a method of producing a sheet in which a collection of synthetic resin hollow balls bonded by frictional heat is covered with a collection of acetylene black aggregates bonded by friction welding.
4. The method for producing the sheet according to claim 1 comprises the steps of: The carbon black recited in claim 1 is Ketjen black, and the method of using the Ketjen black as the carbon black recited in claim 1 and continuously carrying out all of the treatments in the five steps recited in claim 1 is a method of producing a sheet in which a collection of synthetic resin hollow balls bonded by frictional heat is covered with a collection of Ketjen black aggregates bonded by friction welding.
5. A method for bonding the sheet prepared by the method according to claim 1 to the surface of a substrate or a part includes the steps of: The sheet produced by the method according to claim 1 is placed on the surface of a substrate or a part, and a compressive stress is applied uniformly to the entire surface of the sheet. As a result, first, a group of aggregates joined by friction welding covering the surface of the sheet comes into contact with the surface of the substrate or the part. Then, the compressive stress is applied to the group of aggregates joined by friction welding, and a part of the group of aggregates joined by friction welding that comes into contact with the surface of the substrate or the part is elastically deformed, and the elastically deformed aggregates joined by friction welding are deformed.
2. A method for joining a sheet produced by the method described in claim 1 to a surface of a substrate or a component, wherein a portion of the collection of gates penetrates into a recess in the unevenness of the surface of the substrate or the component and fills the recess in the surface, and further wherein the compressive stress is applied to the collection of aggregates joined by the friction welding, generating frictional heat at a contact portion where the collection of aggregates joined by the friction welding comes into contact with the surface of the substrate or the component, and the frictional heat bonds the collection of aggregates joined by the friction welding to the surface of the substrate or the component.
Citation Information
Patent Citations
Extruded blow container
JP2020183281A
Synthetic resin container and preform
JP2022119649A